Validitas LKS berorientasi HOTS (high order thinking skill) dalam model inkuiri terbimbing pada materi hakikat fisika dan prosedur ilmiah, pengukuran, serta vektor di kelas X SMA /MA - Aprilia Cahaya; silvi yulia sari; yenni darvina (Universitas Negeri Padang, 2019)
Education plays an important role in improving Human Resources who can follow the development of science and technology globally, and requires people who have high skills and critical thinking. Conditions in schools have not yet implemented the guided inquiry learning model and the application of HOTS in schools is not optimal because it has not been able to improve students' high-level thinking. One solution based on observing this problem is to use HOTS-oriented worksheets using the guided inquiry model, the guided inquiry model is one of the learning models that requires students to search for and find their own knowledge. The purpose of this study is to overcome this problem by creating a HOTS-oriented worksheet in a guided inquiry model and finding out the results of validity. The research conducted is a type of research and development (R&D). Using borg and gall as the object of research is HOTS-oriented worksheets in the guided inquiry model. The data source of this research is the result of validation from experts including physics lecturers at FMIPA UNP as validator. Based on data analysis from research, it is very valid with an average validity value of 84.2. So the results of the study show that HOTS-oriented Student Worksheets in the guided inquiry model of the nature of physics and scientific procedures, measurements, and vectors of Class X SMA / MA have been made suitable for use in the physics learning process, because they meet the basic feasibility of the results of the experts' validation.